Pierre-Henri de Valencienne: Theorist and Painter - Ivasyutina, Marina A. (Actual Problems of Theory and History of Art, 2014)
Pierre-Henri de Valencienne is one of the most prominent painters of Neo-Classicism, who integrated the principles of the historical landscape painting into one theoretical system. His landscape paintings, the specimen of ideal and beautiful Nature, are constructed in accordance with the strict rules of Classicism and are rooted in the art of Claude Lorrain. But Valencienne is also the author of the openair studies, in which one can notice the early signs of spontaneity and freshness of the Impressionistic works. The article deals with the problem of contradiction between Valencienne’s theoretical heritage and his creative work
Keywords: Classicism; landscape; Pierre-Henri de Valencienne; new vision; open-air painting